Innowacyjność jako czynnik rozwoju regionu - Smalec, Agnieszka (Innovations as a Region Development Factor, 2008)
The regions in Poland are facing the serious challenge of the growing competition and strong dynamic of globalization processes. The knowledge-based economy relies on both information society and innovations, new technologies. However, it is not enough to respond to changes but cause them by implementing innovations. The local governments' policy based on innovations has a very important impact on region's development and the strengthening its competitive position. The innovation consciousness and education are the bases for building the knowledge-based region. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 65-71